The Modum-ED Trial Protocol: Comparing Compassion-Focused Therapy and Cognitive-Behavioral Therapy in Treatment of Eating Disorders With and Without Childhood Trauma: Protocol of a Randomized Trial - Vrabel, KariAnne R.; Wampold, Bruce; Quintana, Daniel S.; Goss, Ken; Waller, Glenn; Hoffart, Asle (Frontiers in Psychology, 2019)
Background: The combination of eating disorder (ED) and the experience of childhood trauma leads to significant impairment and suffering. To improve treatment, it is critically important to study treatment effects and the mechanism of these effects. The overall aim of the current project is; (1) to build knowledge on how to best treat patients with ED with and without childhood trauma, (2) to develop our understanding about how change happens for these patients. We will do this by comparing two treatment models; (1) Compassion-Focused Therapy (CFT) and (2) Cognitive-Behavioural Therapy (CBT) for ED. This paper describes the development, design and implementation of the trial. Methods/design: Patients included in this randomized controlled trial will satisfy DSM-5 criteria for ED and approximately half of the patients will in addition have a history of childhood trauma. A total of 144 patients who have received either CFT or CBT are followed up one year after completion of the treatment. The study will collect a rich dataset of outcome measures at four time points, and process, sub-outcome and neurobiological measures at 13 time points. All patients will be assessed with the same clinical instruments based on current state-of-the-art methods. The primary outcome will be percentage of recovery of ED, while secondary outcomes will relate to treatment effects on trauma symptoms, general symptoms and quality of life. Discussion: This trial will make an important contribution to the need for evidence of effective treatment for patients with ED with or without childhood trauma. Ethics and dissemination: The project is approved by the South-Eastern Regional Committee for Medical and Health Research Ethics (REC;2014/836). Registration details: Clinical Trials identifier: NCT02649114